Mentoring conversations in preservice teacher supervision: knowledge for mentoring in categories of participation. Issue 1 (1st January 2022) - Nielsen, Wendy; Tindall-Ford, Sharon; Sheridan, Lynn
ABSTRACT: The purpose of this study was to elaborate the knowledge of the supervising teacher as enacted through mentor-mentee conversations that occur during practicum. An interpretivist framework using Clarke et al.'s (2014) Categories of Participation was used to consider how supervising teacher knowledge manifests in mentoring conversations with the preservice teacher. Case study methods captured conversations in situ when dyad pairs (n = 5) discussed a particular lesson developed and taught by the preservice teacher. The results illustrate three Categories of Participation as most frequent, providing insight into supervising teachers' knowledge base. An important finding from this study is the value of mentoring conversations for 'making visible' classroom teacher practices and knowledge to the preservice teacher during the practicum, which has implications for the professional development of supervising teachers.